(untitled) (diségno, 2020)
Being an architect today, in the presence of the great masters of history, raises questions about the objective existence of a measurable and replicable cosmic harmony. In essence, this is a theme of remote origins, in which man questions the existence of Beauty as an objective value: whether it is inspired by the transcendence of the Platonic idea or by the immanence of the Aristotelian universal. In this paper we analyze some works that have stood the test of time: they are products of a culture different from ours but they have developed a universal language that goes beyond the conventions codified by those who produced them and by those who admire them today. In this context, we present the case study of the Desiderio Abbey of Montecassino, a medieval building that has been lost. Today, on its site stands a modern building whose features reflect the project of the 17th-18th century. The majesty of the original building comes to us from the chronicles of the time and somehow it still reverberates in the current layout of the abbey. The aim of this study is to trace the original design model which inspired Abbot Desiderio to create his work. The survey uses the tools and methods of drawing, surveying and analyzing the graphic documents received by us thanks to the cataloging and conservation of historical archives.